Gold mining greenhouse gas emissions, abatement measures, and the impact of a carbon price. (15th March 2022) - Ulrich, Sam; Trench, Allan; Hagemann, Steffen
Abstract: Global greenhouse gas (GHG) emissions from gold mining exceed 100 Mt CO2 -e annually, with country emissions intensity from 129 to 2754 kg CO2 -e/oz, yet clear knowledge gaps remain regarding country contributions, emissions reduction potential, and impact of carbon pricing. The cost impacts upon global gold miners of the introduction of a hypothetical US50/t CO2 -e and US100/t CO2 -e carbon price are quantified and are affordable. Carbon price impacts vary markedly between countries, with a US100/t CO2 -e price increasing gold production costs on average by US13 per ounce in Finland and up to US275/oz in South Africa. The research method aggregated 2018 mine-specific GHG emission and production data to the country level, allowing carbon price impacts to be quantified. Global adoption of carbon pricing changes the relative cost competitiveness of countries, having policy implications. Clean energy substitution and energy efficiencies, including new mining technologies, are at the forefront of the gold sector responses to reduce emissions. The reduction in GHG emissions from energy substitution of the mine's primary energy source is up to 46%. The most significant reductions in GHG emissions from energy efficiencies are in underground mines from ventilation and cooling, up to 24%. Gold companies that reduce their carbon footprint benefit from a lower cost of capital. Clear potential exists for a shift towards a cleaner, decarbonised global gold industry. Graphical abstract: Image 1 Highlights: GHG emissions intensity, production costs and carbon pricing analysed for the gold industry globally The gold industry can afford a US100/t CO2 -e carbon price Carbon pricing of US100/t CO2 -e would impact gold production costs between US13–275/oz Carbon prices disproportionately impact gold production costs in developing countries GHG abatement curves indicate the effective role of energy substitution in emissions reduction